Racial/ethnic variation of APOE alleles for lobar intracerebral hemorrhage. (31st July 2018) - Sawyer, Russell P.; Sekar, Padmini; Osborne, Jennifer; Kittner, Steven J.; Moomaw, Charles J.; Flaherty, Matthew L.; Langefeld, Carl D.; Anderson, Christopher D.; Rosand, Jonathan; Woo, Daniel
Abstract : Objective: APOE ε2 and ε4 alleles have been associated with lobar intracerebral hemorrhage (ICH) in predominately white populations; we sought to evaluate whether this held true among black and Hispanic populations. Methods: The Ethnic/Racial Variations of Intracerebral Hemorrhage study is a prospective, multicenter case-control study of ICH among white, black, and Hispanic participants. Controls were recruited to match cases based on age, ethnicity/race, sex, and geographic location. APOE genotyping and ICH location was determined blinded to clinical data. Results: There were 907 cases of lobar ICH and 2, 660 controls with APOE results. Both APOE ε 2 (odds ratio [OR] 1.5, 95% confidence interval [CI] 1.1–2.0, p = 0.01) and APOE ε 4 (OR 2.0, 95% CI 1.5–2.6, p < 1 × 10 −4 ) were associated with lobar ICH among white participants. Among black participants, neither APOE ε 2 (OR 1.0, 95% CI 0.7–1.5, p = 0.97) nor APOE ε 4 (OR 1.0, 95% CI 0.7–1.4, p = 0.90) were independent risk factors for lobar ICH. Similarly, among Hispanic participants, neither APOE ε 2 (OR 1.0, 95% CI 0.6–1.8, p = 0.89) nor APOE ε 4 (OR 1.2, 95% CI 0.8–1.7, p = 0.36) were associated with lobar ICH. Hypertension was a significant risk factor for lobar ICH in all 3 racial/ethnic groups. Conclusion: In contrast to Caucasian patients, in which amyloid risk factors predominate in lobar ICH, we found that hypertension was the predominant risk factor for lobar ICH. While APOE alleles are a risk factor for lobar ICH in white patients, they appear to have a much lower effect in lobar ICH in African American and Hispanic American populations. This suggests APOE ε 2 and APOE ε 4 do not affect lobar ICH risk homogeneously across ethnic populations. In addition, hypertension has a prominent role in lobar ICH risk, particularly among minorities.